7 Penerapan Total Quality Management (TQM) Terhadap Kualitas Pelayanan Penumpang - Kifni Yudianto (Jurnal Manajemen Dirgantara, 2019)
The implementation of the Total Quality Management (TQM) at PT Angkasa Pura II (Persero) Pontianak Supadio International Airport. This study uses qualitative descriptive research. The results of this study indicate that the application of Total Quality Management to the quality of service of PT Angkasa Pura II (Persero) has been well implemented. The implementation of Total Quality Management has been granted rights to passengers in accordance with the standards of passenger service while at the airport. Companies still need to make continuous improvements, especially in adding the number of personnel needs